Teaching styles and academic performance in university education (Revista Innova Educación, 2021)
The research had the purpose of determining the relationship between the teaching style and academic performance in the students of the Professional School of Initial Education of the National University of Altiplano, Puno. Methodologically, the research is descriptive and correlational. The sample consisted of 233 students to whom a questionnaire with 71 indicators was applied, corresponding to the teaching styles, and a document analysis guide was used for the academic performance variable. To determine the correlation, the Spearman correlation coefficient, ρ (rho). The results show a moderate positive correlation between teaching styles and academic performance, which are represented in a 0.452 * relationship. In conclusion, the higher the level of applicability of the different teaching styles, the better and the higher the students' academic performance.
Keywords: learning; academic performance; education; teaching styles; evaluation